Bridging the gap between face-to-face and virtual class: What to be considered in the course of scientific writing? - Dwigustini, Retno; Halim, Nurhasanah; Susilawati, Susilawati (Journal of Research in Instructional, 2024)
This systematic review attempts to summarize articles that provide information for lesson planners and curriculum development to consider in the design and development of virtual classes for scientific writing. A qualitative research methodology was employed to analyze the information gathered to answer two research questions. The protocol in the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) was incorporated to provide a carefully planned and recorded systematic review to ensure consistency, openness, accountability, and integrity of review articles. The results signify considerations for designing scientific writing, including personal assistance and guidance for the preparation of paper writing and submissions. The analyzed articles also recommend facilitating students with their preference-based activities and building interactivity.